Editorial: Volume 1 - Bintliff, John (Journal of Greek Archaeology, 2016)
Why another new journal? Since my PhD research I have specialised in Landscape Archaeology in the Mediterranean, and over the decades this field has broadened in a totally unpredictable fashion. Originally it was developed to locate places mentioned in Classical texts, then Prehistory was added by the end of the 19th century, with occasional mention of Medieval sites. With the advent of intensive survey in the late 1970s, field-by-field study of the Mediterranean landscape inescapably recorded pottery scatters of every age up to the Post-Medieval era, although it has been a slow progression for post-Roman sites to be given the same attention as earlier eras. The serious study of deserted Medieval and Early Modern villages and farms could be added to the well-known Roman villas and Classical farmsteads recognised from the start of intensive survey programmes. Then the survival of substantial ruined buildings on post-Roman sites called for their documentation and contextualising into similar buildings still rarely observable in existing communities. Just as ancient texts had been invaluable from the beginning of landscape archaeology, so now Medieval and later sources could be brought in to give depth to ceramics and houses in the countryside.